MOTHER’S KNOWLEDGE OF THEIR CHILDREN’S ORAL HEALTH - igova, Ralitsa Bogovska-G (International Journal of Medical Science and Dental Health, 2024)
Abstract: Evaluating parental knowledge and practice regarding oral hygiene, feeding habits, and risk factors related to caries is essential, as this projects the parents' outlook toward their children's oral health. Aim: The study aims to assess mothers' knowledge of children up to three years of age about oral health for their children. Materials and methods: The subjects of the study were 90 mothers. Mothers' knowledge was collected after completing a questionnaire including 12 questions about their children's oral health. Results: About 94% of the mothers did not visit a dentist to seek prevention or oral care for their child. 29% of mothers believe that long night feedings with a bottle can cause tooth decay. According to 62.22% of mothers, night breastfeeding and falling asleep at the breast is not a risk factor for caries development. Only 22.22% of all surveyed mothers have heard about early childhood caries. Most mothers (64.44%) do not know that the microorganisms that can cause caries can be transmitted from them to their children. Conclusion: Our survey showed that young mothers need more knowledge regarding their children's oral health. Mothers must be educated and understand their essential role as 'promoters' of good oral health and habits for their children.